Digital-Based Business Sustainability Strategy for MSMEs in Medan City - Abdu Rahman Hakim; Muhammad Ikhsan Harahap; Nur Ahmadi Bi Rahmani (Indonesian Journal of Islamic Economics and Finance, 2026)
This study evaluates digital-based business sustainability strategies among Micro, Small, and Medium Enterprises (MSMEs) in Medan City and identifies internal and external factors affecting business resilience. Using a qualitative descriptive approach, data were collected through in-depth interviews with five MSME owners/managers, supported by observations and documentation. Data validity was ensured through source triangulation and member checking. The analysis employed SWOT analysis along with the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. The results indicate that digital adoption among MSMEs is still developing. While most businesses utilize social media and online marketplaces, digital technology has not yet been fully integrated into comprehensive business strategies. The IFE score of 2.50 reflects a moderate internal condition, with strengths in product innovation and operational flexibility, but weaknesses in digital literacy and human resource capabilities. The EFE score of 2.95 shows that MSMEs are relatively responsive to external opportunities, particularly the rapid growth of e-commerce and evolving consumer behavior. SWOT analysis places MSMEs in Quadrant II (Weakness–Opportunities), indicating that significant external opportunities are not yet supported by adequate internal capacities. Accordingly, a turnaround (WO) strategy is recommended, emphasizing the utilization of digital opportunities to address internal weaknesses through improving digital literacy, enhancing workforce competencies, and integrating technology into business operations. The study concludes that digitalization is a key driver of business sustainability. However, its effectiveness depends on strengthening internal capabilities and implementing adaptive strategies that enable MSMEs to achieve long-term sustainable growth and maintain competitiveness in an increasingly digital business environment.